Simplified equivalent aggregation framework for impedance network modeling of MMC-HVDC systems with grid structural considerations - Yanxu Wang; Guoqing Li; Yechun Xin; Tuo Wang; Shouqi Jiang; Weiru Wang; Yupeng He (International Journal of Electrical Power & Energy Systems, 2025)
Modular Multilevel Converter (MMC)-based Multi-terminal High-voltage Direct Current (MTDC) systems have gained widespread application in power transmission, where analyzing their wideband stability is critical for enhancing DC grid operational performance. This study focuses on addressing wideband stability challenges in MTDC systems. Recognizing limitations in existing impedance modeling and network analysis approaches, the research first establishes a DC-side wideband impedance model for MMC stations by incorporating their multi-harmonic coupling characteristics. Subsequently, a generalized impedance network simplification methodology is proposed, applicable to two-terminal, three-terminal, and four-terminal MMC-HVDC system configurations — extensible to systems with higher terminal counts. Furthermore, this paper systematically analyzes the impact of system parameters (e.g., line lengths, control gains) on wideband stability and develops a coordinated suppression strategy balancing oscillation mitigation and dynamic performance enhancement. Finally, electromagnetic transient (EMT) simulations validate the methodology’s accuracy and effectiveness, providing a theoretical framework and technical guidelines for ensuring stable MTDC grid operation.